Sentence repetition span in primary progressive aphasia and Alzheimer's disease: Insights from preliminary results - Arslan, Seçkin; Plonka, Alexandra; Mouton, Aurélie; Lemaire, Justine; Cogordan, Magali Payne; Sacco, Guillaume; Manera, Valeria; Gros, Auriane; Meunier, Fanny (Frontiers in Communication, 2022)
Primary Progressive Aphasia (PPA) is a form of neurocognitive disorder ascribed to cortical atrophy impacting language abilities. It is widely classified into three main variants: logopenic PPA (lvPPA), the semantic variant of PPA (svPPA), and the non-fluent PPA (nfvPPA) showing different impairment patterns across variants. However, in the early phases of PPA, it is not always easy to dissociate different PPA variants and distinguish PPA from other neurodegenerative disorders. One characteristic language symptom that seems to distinguish PPA, especially the logopenic variant, is impaired sentence repetition. Nonetheless, studies examining sentence repetition in PPA, and Alzheimer’s disease (AD) more broadly, have resulted in mixed findings. To be able to better understand the working memory-intensive nature of sentence repetition deficits, we designed a sentence repetition span task. We seek to understand (i) whether three diagnostic groups (lvPPA, svPPA and AD) encounter greater sentence repetition difficulties than the controls, and (ii) whether using a span task design, in which the number of content words increases as the span length increase, would help dissociate PPA variants from AD type dementia. In this study we administered a sentence repetition span task to four groups of French-speaking individuals with lvPPA (n = 14), svPPA (n = 5), and with AD (n = 13) and their age-matched healthy controls (n = 61). The results showed that all the three diagnostic groups (lvPPA, svPPA, and AD) performed equally poorly as compared to the controls on the repetition span task virtually in all measures (i.e., sentence span, number of content words, number of omission and substitution errors). One intriguing finding was that the lvPPA group produced an exalted number of phonological errors during repeating sentences, while this type of error was somewhat moderate in the svPPA group and only minimal in the AD group. We conclude that sentence repetition difficulty in PPA and AD should be modulated by working memory capacity, as our participants undoubtedly demonstrated greater difficulty as the span length increased. However, we note that working memory-intensive sentence repetition deficits based on the number of content words might not reveal critical diagnostic differences between the neurodegenerative groups.